Prevalence of mental ill health, traumas and postmigration stress among refugees from Syria resettled in Sweden after 2011: a population-based survey - Tinghög, Petter (BMJ Open, 2017)
OBJECTIVES: To estimate the prevalence of and associations between anxiety, depression, post-traumatic stress disorder (PTSD), low subjective well-being (SWB), potential traumas and postmigration stress among refugees from Syria resettled in Sweden. DESIGN: A cross-sectional and population-based questionnaire study based on a known and complete sample frame. The survey included multiple measures of mental ill health and factors of particular relevance for refugees. Weighted analyses were conducted to calculate representative prevalence rates and associations. Associations were investigated through a series of logistic regression analyses. All analyses were supplemented with robust 95% CIs. SETTING: Sweden. PARTICIPANTS: A random sample of 1215 individuals (response rate 30.4%) from Syria aged 18–64 years that were granted residency in Sweden on grounds of asylum between 2011 and 2013. MAIN OUTCOME MEASURES: Anxiety, depression, PTSD and low SWB were assessed through Hopkins Symptom Checklist, Harvard Trauma Questionnaire and WHO-5 Well-being Index, using established cut-offs. RESULTS: A majority of the participants met the criteria for at least one of the studied types of mental ill health, and the comorbidity was high. Depression was the most the common type with 40.2% (95% CI 36.9% to 43.3%), followed by low SWB with 37.7% (95% CI 34.8% to 40.1%), anxiety with 31.8% (95% CI 29.2% to 34.7%) and PTSD with 29.9% (95% CI 27.2% to 32.6%). Refugee-related potentially traumatic events (PTEs) experienced before or during migration was common as was substantial levels of postmigration stress. Most types of refugee-related PTEs, especially being exposed to interpersonal violence, and postmigration stress were associated with increased risks for anxiety, depression, low SWB and PTSD. CONCLUSIONS: Mental ill health, in terms of anxiety, depression, low SWB and PTSD, are highly elevated and comorbid among refugees from Syria. Increased attention from multiple societal sectors to adequately support Syrian refugees’ mental health needs, promoting recovery and reducing postmigration stress are needed.